2004
DOI: 10.2337/diabetes.53.10.2684
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Contribution of HLA-DR and -DQ Haplotypes to Susceptibility to Adult- and Childhood-Onset Type 1 Diabetes in Japanese Patients

Abstract: To clarify heterogeneity in Japanese adult-onset type 1 diabetes, we analyzed the HLA-DR and -DQ haplotypes, depending on the clinical phenotype, and compared them with those in childhood-onset type 1 diabetes (CO). The patients in a previously reported Ehime Study were divided into subgroups by the mode of onset of diabetes: 68 acute-onset type 1 diabetic patients (AO) and 28 slowly progressive type 1 diabetic patients (SO). HLA haplotypes were compared with those of 80 CO patients and 190 control subjects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 42 publications
5
56
3
3
Order By: Relevance
“…In our case, HLA typing of DR was DR-4 and DR-8 which is an increased risk for Japanese juvenile-onset type 1 diabetes [10]. In addition, serological examination showed positive GAD and IA-2 antibodies.…”
mentioning
confidence: 84%
“…In our case, HLA typing of DR was DR-4 and DR-8 which is an increased risk for Japanese juvenile-onset type 1 diabetes [10]. In addition, serological examination showed positive GAD and IA-2 antibodies.…”
mentioning
confidence: 84%
“…Conversely, the DR8 haplotype confers susceptibility to Japanese T1D (Awata et al, 1992;Kawabata et al, 2002;Kobayashi et al, 1993;Murao et al, 2004;Ohtsu et al, 2005;Yasunaga et al, 1996) and is present only in Japanese and Korean T1D (Thomson et al, 2007). However, some studies have found no evidence that the DR8 haplotype confers susceptibility to Japanese T1D (Maruyama et al, 1994;Murao et al, 2004;Tanaka et al, 2002). Table 5 shows the phenotype frequency of the DR8 haplotype and the mean onset age of T1D in previous studies.…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 96%
“…are the most frequently observed susceptibility haplotypes in the Japanese (Awata et al, 1992;Kawabata et al, 2002;Kobayashi et al, 1993;Maruyama et al, 1994;Murao et al, 2004;Tanaka et al, 2002;Yasunaga et al, 1996). However, studies conducted before the discovery of fulminant T1D may have included patients with fulminant T1D.…”
Section: Hla Class II Genes and T1d In The Japanese Populationmentioning
confidence: 99%
See 2 more Smart Citations